Constructivist Peer Review in Music Theory and Composition Courses: Technologies and Practice - Brendan McConville (Journal of the Association for Technology in Music Instruction, 2021)
This article considers the supporting technologies and practices for effective semi-anonymous peer review in traditional music theory and composition-related courses: orchestration, arranging, and composition. A coordinated approach probes two questions nested within one broad case study: (1) does the use of peer review in music theory and composition-related courses create meaningful, constructivist-inspired learning experiences, and (2) what web technologies can efficiently and effectively accomplish its activities? The article first provides a constructivist theoretical framework; next, it explains the methodologies, technologies, and resulting feedback from using peer review in a three-course study; and finally it provides concluding remarks on the many benefits and manageable problems that can arise in the social constructivist peer review music classroom.
Keywords: constructivism; technology; peer review; music theory; arranging; orchestration; composition; pedagogy; assessment